2017
DOI: 10.1007/s13187-017-1193-8
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Education on the Early Diagnosis of Breast and Cervix Cancer on the Women’s Attitudes and Behaviors Regarding Participating in Screening Programs

Abstract: The objective of this paper was to define the effect of education on the early diagnosis of breast and cervix cancer on the women's attitudes and behaviors regarding participating in Cancer Early Diagnosis, Screening and Training Centers-CEDSTC screening programs. This semi-experimental study was completed with 342 women. The data were collected with forms "Champion's Health Belief Model Scale Breast Cancer-HBMSBC" and "Health Belief Model Scale for Cervical Cancer and the Pap Smear Test-HBMSCCPST." When the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 28 publications
1
18
1
1
Order By: Relevance
“…Lack of access to female condoms was also a barrier to the current intervention. Previous studies have indicated that there was a relationship between taking Pap smears and perceived susceptibility, severity, Benefits, barriers, and self-Efficacy [19,30].…”
Section: Discussionmentioning
confidence: 99%
“…Lack of access to female condoms was also a barrier to the current intervention. Previous studies have indicated that there was a relationship between taking Pap smears and perceived susceptibility, severity, Benefits, barriers, and self-Efficacy [19,30].…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Table 2 , the gathered studies were published between 2014 and 2019, and were conducted in Malaysia (n = 1) [ 16 ], Iran (n = 7) [ 19 , 47 , 48 , 49 , 50 , 51 , 52 ], United States (n = 6) [ 53 , 54 , 55 , 56 , 57 , 58 ], Turkey (n = 4) [ 10 , 11 , 59 , 60 ], Israel (n = 1) [ 9 ], United Arab Emirates (n = 1) [ 61 ], China (n = 1) [ 62 ], and India (n = 1) [ 63 ]. In addition, the participants were aged 18 years and above.…”
Section: Resultsmentioning
confidence: 99%
“…A study in Iran stated that the PST rate increased in the group trained with the booklet (pre-education = 51.2%, post-education = 74.4%), in the conference-training group (pre-education = 62.1%, post-education = 74.4%) and did not change in the control group (pre-education = 46.5%, post-education = 46.5%; Rezaei et al, 2004). The studies were emphasised that education was effective in PST behaviours of women (Kocaöz et al, 2018;Love & Tanjasiri, 2012). Similar to other researches findings, it was observed that education is an important factor to increase PST rate although the training methods were different.…”
Section: Discussionsmentioning
confidence: 99%